Terra de ninguém! o que será do pae santo afonso com a implantação do terminal portuário de uso privado – tup Abaetetuba? - VASCONCELOS, Tatiane Rodrigues de (Universidade Federal do Pará, 2023)
The research has as a reference the recognition of the right to territory for traditional peoples and communities in the Santo Afonso Agroextractivist Project, located in the Xingu Island, in the municipality of Abaetetetuba/Pa, in the scope of the National Program of Agrarian Reform through the National Institute of Colonization and Agrarian Reform-Incra in partnership with the Secretary of the Union Patrimony. In order to identify the paths to the recognition of rights for traditional peoples and communities, the research goes through the indicators of the creation of the settlement, including, describes about the sparse legislation. The object of analysis is the settlement PAE Santo Afonso, located in the municipality of Abaetetuba-Pará, on the Xingu islet and the confrontation of struggles and resistance in the installation of the port enterprise identified as Tup-Abaetetuba-PA owned by the company Cargill. The study presents the characterization of the PAE Santo Afonso with regard to the riverside way of life and the normative adjustments since the implementation Ordinances, in addition to the reflection of Law No. 13,465/2017 with the Regulatory Decree No. 9,311/2018 With regard to methodology the study had a qualitative and quantitative direction using multi-methods, which includes direct observation, focus groups and suggestion of participant interviews. The research subjects were the riparians of the Community Vilar, Xingu and others from the Association of the Pae Santo Afonso. The qualitative data were analyzed from the bibliographic references, document of constitution of the PAE, as the field research. Thus, based on the analysis of the materials collected, it was found that the site is legally a differentiated Project Ambientally and the subjects that live there struggle and resist in an attempt to maintain decent housing.